2008
DOI: 10.1590/s1413-86702008000100012
|View full text |Cite
|
Sign up to set email alerts
|

Anatomopathological study in BALB/c mice brains experimentally infected with Toxoplasma gondii

Abstract: Toxoplasmosis is one of the most important diseases of the nervous central system, leading to severe symptoms and, many times, irreversible sequelae. This work demonstrated the main anatomopathological lesions caused by Toxoplasma gondii in brains from experimentally infected BALB/c mice. We analyzed 51 cases of mice that developed toxoplasmosis after experimental infection by intraperitoneal inoculation of blood, amniotic liquid and cerebrospinal fluid from fetuses, newly born children and pregnant women with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…Blood samples were collected before specific medication was given to NB. These samples were taken to determine the presence of a parasite by PCR or experimental inoculation in mice (using according to Silva et al [ 65 ]. PCR was performed according to the following protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Blood samples were collected before specific medication was given to NB. These samples were taken to determine the presence of a parasite by PCR or experimental inoculation in mice (using according to Silva et al [ 65 ]. PCR was performed according to the following protocol.…”
Section: Methodsmentioning
confidence: 99%
“…However, it may convert to a chronic phase without symptoms; this phase being mostly localized in the brain (14). This is because T. gondii is able to pass the blood-brain-barrier and settle in the central nervous system (brain) and establish cysts including bradyzoites (17) that escape the immune system (3) and lead to chronic infection in the brain, and present various psychoneurological disorders (12,18,19).…”
Section: Resultsmentioning
confidence: 99%
“…Also, some reports demonstrated diffuse edema and congestion. However, in some studies no significant edema or necrosis was reported in parallel to the observed hemorrhage (19,48). Diffuse meningoencephalitis, in the white and gray matter has also been seen (19).…”
Section: Anatomopathological Changesmentioning
confidence: 99%